The use of erythropoietin in renal failure. Issue 783 (January 1991) - Macdougall, I. C.; Hutton, R. D.; Coles, G. A.; Williams, J. D.
Abstract : The treatment of renal anaemia by recombinant human erythropoietin (EPO) is now well established. Several studies have examined the pharmacokinetics and efficacy of the drug given intravenously, intraperitoneally and subcutaneously and there is increasing evidence that the subcutaneous route has several advantages including the requirement for a lower dose. It is also important to stress the need for careful determination of baseline iron status of all patients before commencing EPO therapy. In the long term the extremely high iron stores of transfusion dependent patients will disappear. In the short term, however, the majority of the patients whose serum ferritin is less than 100 micrograms/l will require iron supplementation to allow an appropriate haemoglobin response. Alternatively, a fall in transferrin saturation to less than 20% is certainly an indication for iron supplementation and if oral iron therapy is not adequate then intravenous preparations may have to be considered. Although the anaemia of renal failure can be fully corrected by EPO, partial correction may be sufficient to reverse the problems of reduced exercise capacity, myocardial ischaemia and cardiomegaly which are frequently associated with end-stage renal disease. Partial correction will also result in a lesser rise in whole blood viscosity and, in turn, possibly reduce hypertension, thrombosis and increased peripheral resistance and thus lessen the side effects of EPO therapy.